Study protocol of a multicentre cohort pilot study implementing an expanded preconception carrier-screening programme in metropolitan and regional Western Australia. Issue 6 (16th June 2019) - Ong, Royston; Edwards, Samantha; Howting, Denise; Kamien, Benjamin; Harrop, Karen; Ravenscroft, Gianina; Davis, Mark; Fietz, Michael; Pachter, Nicholas; Beilby, John; Laing, Nigel
Abstract : Introduction: Preconception carrier screening (PCS) identifies couples at risk of having children with recessive genetic conditions. New technologies have enabled affordable sequencing for multiple disorders simultaneously, including identifying carrier status for many recessive diseases. The aim of the study was to identify the most effective way of delivering PCS in Western Australia (WA) through the public health system. Methods and analysis: This is a multicentre cohort pilot study of 250 couples who have used PCS, conducted at three sites: (1) Genetic Services of Western Australia, (2) a private genetic counselling practice in Perth and (3) participating general practice group practices in the Busselton region of WA. The primary outcome of the pilot study was to evaluate the feasibility of implementing the comprehensive PCS programme in the WA healthcare system. Secondary outcome measures included evaluation of the psychosocial impact of couples, such as reproductive autonomy; identification of areas within the health system that had difficulties in implementing the programme and evaluation of tools developed during the study. Ethics and dissemination: Approval was provided by the Women and Newborn Health Service Human Research Ethics Committee (HREC) at King Edward Memorial Hospital for Women (RGS0000000946) and the University of Western Australia (UWA) HREC (RA/4/20/4258). Participants may choose to withdraw at any time. Withdrawal will in no way affect participating couples' medical care. Study couples will be redirected to another participating health professional for consultation or counselling in the event of a health professional withdrawing. All evaluation data will be deidentified and stored in a password-protected database in UWA. In addition, all hard copy data collected will be kept in a locked cabinet within a secure building. All electronic data will be stored in a password-protected, backed-up location in the UWA Institutional Research Data Store. All evaluative results will be published as separate manuscripts, and selected results will be presented at conferences.